LINGUISTIC VARIETIES IN ECONOMICS AND OTHER REGISTERS - I Gusti Ayu Vina Widiadnya Putri (Fakultas Bahasa Asing (FBA) Universitas Mahasaraswati Denpasar, 2016)
ABSTRACT The title of this article is “Linguistic Varieties in Economic and other Registers”. This article tries to analyze ad discuss about the meaning of words varieties used in register of Economics that can be also used in other registers. Many words in register of economics has specific meaning, which are only used in economics section, but in other side, those word can be also used on other context of situation. The words of economics register were taken from the economics articles or business magazine, in Jakarta Post Newspaper and Bali Advertiser magazine. The analyzing of Language Varieties in Economics Register focuses on the following points of problems: (1) the meaning of words varieties that are used in Registers of Economics. (2) The varieties of words in Register of Economics that can be also used in other Register. In analyzing the language varieties used in register of economics, this research applies the sociolinguistics theory, taken from Peter Trudgill (1974) in this book entitled An Introduction to Language and Society as main theory. The theory is supported by other theories that are considered relevant to the topic of discussion in this article. Based on the result of the research and analysis, it is found that are two kinds of words used in register of economics, they are common words are the word usually used in common situation and specific words are the words used in specific situation. Besides that, the word in register of economics can be used in other registers such as: register of culture, register of politics, register of medical, register of education, register of engineering, and register of government’s affair. Key Words : Context of Situation, Register and Economics.